Yield of cherry tomatoes as a function of water salinity and irrigation frequency - Alexandre N. Santos; Ênio F. de F. e Silva; Gerônimo F. da Silva; Janice M. C. Barnabé; Mario M. Rolim; Daniel da C. Dantas (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of brackish water in agriculture can cause salinization of soils and reduce plant yield. This problem can be minimized by hydroponic cultivation, which improves plant development. The aim of this study was to evaluate the yield of cherry tomatoes grown in hydroponic system with substrate under salinity levels of the nutrient solution (NS), exposure time to salinity and irrigation frequency. The experiment was conducted in a greenhouse, in a randomized complete block design, in a 6 x 2 x 2 factorial scheme with five replicates: six salinity levels of NS prepared with brackish water (3.01; 4.51; 5.94; 7.34; 8.71 and 10.40 dS m-1); two exposure times to NS (60 and 105 days) and two irrigation frequencies (one irrigation per day and irrigation every two days). Yield and production components of cherry tomatoes cv. 'Rita' were evaluated. NS salinity affected plant yield, reducing fruit production, which was more significant when plants were subjected to a longer time of exposure to salinity. There was no difference between NS applications on fruit production, when these applications were performed once a day or once every two days.